El rol de la escuela en la construcción del desarrollo rural: experiencias argentinas - Natalia Millán (Universidad Nacional, Costa Rica, 2007)
Social processes such as globalization, non territorial productive processes, sprouting of local development and the arising of knowledge society -even in the rural context- bring serious implications for rural education, which has to face a process of modernization and reconstruction in order to avoid the exclusion of current social processes. Different aspects of educational politics in Argentinean rural sectors are analyzed in this article, and a reflection is made about this analysis in order to determine the path to follow in the future.